Reactions of morita-baylis-hillman acetates with huisgen zwitterions: a novel strategy for the synthesis of ?-amino acid derivatives - Jose, Anu; Paul, Rony Rajan; Mohan, Resmi; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh; Nair, Vijay (Synthesis, 2009)
The reaction of Huisgen Zwitterion with Morita–Baylis– Hillman acetates afforded b-amino acid derivatives.
Keywords: b-amino acid; Huisgen zwitterion; Morita–Baylis–Hillman acetate